Benefits of exercise in older persons at primary level - Annie Kunda; Seyi L. Amosun (AOSIS, 1998)
The National Department of Health invited comments on proposed policy guidelines on the prevention of physical inactivity in older persons at primary level. The guidelines recommended the use of exercises which are dynamic, interesting, fun, easily implemented, safe and tailored to suit the individual needs. In order to make informed comments on the policy, the aim of this study was to evaluate the impact of the recommended exercise program among older persons in a local community over a six-week period. Promoting physical activity among the participants in the study resulted in marked improvements in systolic and diastolic blood pressures, and dominant hand grip strength. The time taken to perform some selected functional tasks also improved. The findings gave credence to the need to discourage physical inactivity among older persons, but there is need to overcome formidable methodological problems in evaluating the effects of exercise intervention among older persons in the community.